2004
DOI: 10.1158/1078-0432.ccr-04-0565
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exemestane and Tamoxifen in a Postmenopausal Breast Cancer Model

Abstract: Purpose: To optimize treatment strategies for postmenopausal breast cancer patients, we investigated the efficacy of the steroidal aromatase inhibitor exemestane alone or in combination with the antiestrogen tamoxifen in a xenograft model of postmenopausal breast cancer. We also determined the effects of these agents in sequential secondline therapy and the effect of the nonsteroidal aromatase inhibitor letrozole on tumors that progressed on the above treatments.Experimental: Aromatase-transfected human estrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…However, overall tumor growth rate may vary between experiments. In this study, the tumors had initially regressed during treatment with letrozole (30) but grew back more slowly than in other reported investigations (32,36) and had doubled after 32 weeks of treatment. Several mice were sacrificed during the course of the treatment for tumor analysis on weeks 4, 28, and 56.…”
Section: Discussionsupporting
confidence: 40%
See 1 more Smart Citation
“…However, overall tumor growth rate may vary between experiments. In this study, the tumors had initially regressed during treatment with letrozole (30) but grew back more slowly than in other reported investigations (32,36) and had doubled after 32 weeks of treatment. Several mice were sacrificed during the course of the treatment for tumor analysis on weeks 4, 28, and 56.…”
Section: Discussionsupporting
confidence: 40%
“…For this purpose, we have used a model system in which human breast cancer cells expressing the ER and stably transfected with the aromatase gene are grown as tumors in ovariectomized, immunosuppressed mice (30). These tumors are sensitive to the effects of estrogen, antiestrogens, and aromatase inhibitors (30,32,33,(36)(37)(38)(39). However, overall tumor growth rate may vary between experiments.…”
Section: Discussionmentioning
confidence: 99%
“…This is analogous to the two-drug androgen blockade regimens commonly used in advanced prostatic neoplasms (17,18). Murine mammary tumor models suggest that the combination of tamoxifen and exemestane has greater activity than does either drug alone (19). In contrast, the addition of the type I aromatase inhibitors letrozole or anastrazole did not add to the benefit of tamoxifen in this 7,12-dimethylbenanthraceneinduced tumor model.…”
mentioning
confidence: 59%
“…Tumors that progressed during treatment with tamoxifen remained sensitive to second-line letrozole therapy, whereas tumors that progressed on letrozole did not respond to second-line treatment with tamoxifen or fulvestrant. In another series of experiments conducted by the same group using the MCF7Ca model, letrozole was even effective as third-line therapy for a limited period when administered after treatment with tamoxifen and exemestane [102]. The studies showed that although exemestane was more effective than tamoxifen in controlling tumor growth, letrozole as first-line therapy was the most effective treatment overall, both in terms of the degree of tumor suppression and the length of effectiveness of treatment [102].…”
Section: Anti-tumor Activity In Vivomentioning
confidence: 98%